"Argentina is cumbia": Sociocultural Trajectories of Young "Cumbieros" in Urban Peripheries. (13th October 2017) - Silba, Malvina
Abstract : This article analyses the sociocultural trajectories of a group of young men with a low socioeconomic status, all cumbia musicians and producers. The cumbia is one of Argentina's most popular music genres due to its mass dissemination and the social class of the people who have historically enjoyed it. The tension between agency and structure and the relationship between class and culture will be the main themes explored in this article. By focusing on the family, education and work trajectories of these youths, I examine their relationship to cumbia music. Who chooses to become a cumbia musician, and why? I also examine the meanings of "good" versus "bad" music" and the aesthetic and moral parameters used for its definition. This brings me to class belonging and how it shapes musical choices and facilitates disruptive trajectories. The article is based on biographical interviews conducted between 2012 and 2014, combined with participant observation at cumbia dance clubs in Greater Buenos Aires.